Extended lives in global spaces: the anthropology of Yolngu pre‐burial ceremonies⋆. (28th March 2016) - Morphy, Howard
Abstract : The focus is on a recently developed Yolngu ritual, the memorial or memorial service, which celebrates the lives of Yolngu who have achieved a national reputation. Held before the burial ceremony, the memorial service is orientated 'both‐ways' – to the outside as well as to the Yolngu world. Memorial services are analysed in the context of the articulation between Yolngu and the wider Australian society. A diachronically orientated analysis takes into account the longue durée to show how Yolngu create and understand the performance from a historical position and basis of knowledge very different to those of most non‐Yolngu who attend the event. Anthropological research can reveal the durability of local value creation processes that result in very different trajectories of being in an environment of dynamic change.